Parcelacja zdania w świetle badań korpusowych - Stasienko, Anna (Acta Neophilologica, 2023)
Parcelling is the division of a sentence into two or more parts with a full stop. Parcelled construction consists of a main (basic) part and a partcellator. The partcellator comes after a full stop and is semantically and structurally dependent on the main part. The aim of this paper is to show the possibilities of using the Russian National Corpus (together with available tools) in the process of searching for parcelled constructions. The analysis shows that the use of corpus resources and tools is limited to certain types of parcelled constructions.